Pro-vitamin A Carotenoids Stability and Bioaccessibility From Elite Selection of Biofortified Cassava Roots (Manihot esculanta, Crantz) Processed to Traditional Flours and Porridges - Aragón, Ingrid J.; Ceballos, Hernán; Dufour, Dominique; Ferruzzi, Mario G. (Royal Society of Chemistry, 2018)
Cassava biofortification programs have made significant progress in improving pro-vitamin A carotenoid (pVAC) content; however, the nutritional impact of traditional and industrial food processing has not been fully assessed. The effects of fermentation and thermal processing on the stability and bioaccessibility of pVAC from elite selections of biofortified cassava roots were assessed to determine the potential for genotype x processing effects. Unfermented (UF) and fermented (F) flours were produced from 10 genotypes. Gari (G) flour was produced by toasting two fermented cassava genotypes. Bioaccessibility of pVAC was evaluated from finished products (porridges at 22% flour/water) via in vitro digestion. Levels of β-carotene equivalents (β-CE) were 23–43 μg β-CE per g DW among genotypes. F and Gari flours showed higher β-CE retention (p < 0.05) during oven-drying and cooking of porridges compared with UF flours. Bioaccessibility of β-CE (ME%) was 4–15%, across the genotypes and processing. However, contrasting effects of fermentation and thermal processing effects were observed among individual cassava genotypes. These results suggest that genotypic and other factors may impact release and availability of carotenoids and that consideration of both genetics and processing may be warranted in the selection of biofortified cassava cultivars to advance into the application.